Implementing Asset-Based Community Development (ABCD) Approach in Enhancing Qur'anic Literacy Through Tahsin Learning at Gampong Meunasah, Bireuen, Aceh: a Community-Based Participatory Action Research - Dona, Syahri Ramadona; Sukma Widya Puspita; Nurul; Raisa Azyana; Rahmawita; Syahfitri Arika; Riza Maulida (As-sunnah: Jurnal Pengabdian Masyarakat, 2025)
The Qur'an, as Allah's final revelation, serves as the primary source of guidance for Muslims, necessitating proper recitation and understanding for authentic spiritual connection. This study examines the implementation of Asset-Based Community Development (ABCD) approach in enhancing Qur'anic literacy through tahsin learning at Gampong Meunasah, Bireuen, Aceh. The research addresses the critical challenge of inadequate Qur'anic reading proficiency in rural Muslim communities, where 68% of residents demonstrated below-standard tajwid comprehension and 74% lacked consistent access to structured religious education. Employing Community-Based Participatory Action Research (CBPAR) methodology, this study engaged 127 participants across three age groups in a comprehensive 45-day program integrating tahsin, tahfidz, tadabbur, and basic Arabic instruction. The ABCD framework identified and mobilized local assets including the Komunitas Muslimah Wahda Al-Islamiyah, existing religious infrastructure, and intergenerational knowledge transfer mechanisms. Quantitative findings revealed significant improvements: tajwid accuracy increased from 42.3% to 87.6% (p<0.001), Qur'anic memorization capacity expanded by 73%, and comprehension scores improved from M=3.2 to M=4.8 (SD=0.67). Qualitative analysis demonstrated transformative impacts on spiritual identity, social cohesion, and community learning culture. The integration of Maqasid Shariah principles manifested through achievements in hifz ad-din (preservation of religion) via enhanced scriptural access, hifz al-'aql (preservation of intellect) through cognitive development, and hifz al-ijtima'i (preservation of social bonds) via strengthened ukhuwah Islamiyah. The program's sustainability was ensured through local facilitator training, module development, and institutional partnerships. This research contributes an innovative model for community-driven Islamic education that balances authenticity with accessibility, tradition with transformation, demonstrating how rural communities can leverage existing assets to create sustainable religious learning ecosystems.